Malignant melanoma of the anterior mandibular gingiva: a case report - Bhandarkar GOWRI PANDARINATH; Shetty KUSHAL (International Arab Journal of Dentistry (IAJD), 2013)
Oral malignant melanoma is an infrequent neoplasm making up less than 1% of all melanomas; its behavior is more aggressive when compared to melanomas of the skin. We present a rare case of a 50-year-old male patient with a stage II oral malignant melanoma of the anterior mandibular gingiva treated with surgery and radiotherapy.